Hezbollah Rockets and Missiles: Deployment and Defence Programme - Ladislav Kulhánek (Obrana a Strategie, 2018)
The paper addresses the issue of the proliferation of the rocket technology deployed in guerrilla warfare throughout the Near East. It evaluates assumptions and identifies potential regressions with respect to the most recent hot phase in the violent conflict between Hezbollah and Israel, with a focus on primary methods based on rocket shelling and resistance efforts. In comparing the two military forces, Israel emerges as the stronger, even if artillery and tactical ballistic missiles with warheads containing substances defined as weapons of mass destruction were to be deployed as an extreme first measure by Hezbollah, in which case an Israeli or American response would destroy at least parts of Lebanon.